Combining Home Garden, Poultry, and Nutrition Education Program Targeted to Families With Young Children Improved Anemia Among Children and Anemia and Underweight Among Nonpregnant Women in Nepal. Issue 1 (March 2017) - Osei, Akoto; Pandey, Pooja; Nielsen, Jennifer; Pries, Alissa; Spiro, David; Davis, Dale; Quinn, Victoria; Haselow, Nancy
Background: The impact of food-based interventions on child and maternal anthropometry and anemia has not been adequately studied. Objective: This study tested the effect of an enhanced homestead food production (EHFP) program consisting of home garden, poultry raising, and nutrition education implemented over 2.5 years versus control (no intervention) on anthropometry and anemia among children (12-48 months) and their mothers. Methods: An unblinded cluster-randomized controlled trial involving pre- and post-surveys with independent samples was conducted in rural areas of Baitadi District, Nepal. Data (including weight, height/length, and hemoglobin) were obtained from 2106 and 2614 mother–child pairs at baseline and follow-up, respectively. Changes in outcome variables (stunting, underweight, wasting, and anemia among children and underweight and anemia among mothers) were compared between the study groups using mixed-effects logistic regression models. Results: At follow-up, anemia was significantly lower among children (odds ratio, OR [95% confidence interval, CI]: 0.76 [0.59-0.98]) and mothers (OR [95% CI]: 0.62 [0.48-0.82]) in the treatment group compared to the control. Underweight was lower among mothers in the treatment group compared to the control (OR [95% CI]: 0.61 [0.46-0.82]). There was no impact on child anthropometry. Conclusion: The EHFP intervention improved anemia among children aged 12 to 48 months and their mothers in Baitadi District of Nepal. The intervention also reduced underweight among these women, but had no impact on child growth, in this district.